2004
DOI: 10.1023/b:johe.0000038652.65641.0d
|View full text |Cite
|
Sign up to set email alerts
|

A Third World International Health Elective for U.S. Medical Students: The 25-Year Experience of the State University of New York, Downstate Medical Center

Abstract: The Department of Preventive Medicine and Community Health at the State University of New York, Downstate Medical Center instituted a 6-8 weeks third world international health elective for fourth year medical students in 1980. Since that time, some 217 students have participated in a score of third world countries. However, the most popular sites have been India, Kenya and Thailand. The purposes of this elective are to provide fourth year medical students with an opportunity to observe and study the structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 7 publications
0
43
0
Order By: Relevance
“…All study participants revealed a rich learning and training experience in the varied international settings, consistent with prior examinations of global health training experiences. 2,4,5,8 Essays addressing similar themes often approached these subjects differently, reflecting their local context and the personal observations of the author.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All study participants revealed a rich learning and training experience in the varied international settings, consistent with prior examinations of global health training experiences. 2,4,5,8 Essays addressing similar themes often approached these subjects differently, reflecting their local context and the personal observations of the author.…”
Section: Discussionmentioning
confidence: 99%
“…2 In that time, medical educators have posited that international clinical rotations and research experiences benefit trainees by deepening understanding of the complex social, cultural, and economic factors that shape poor physical and mental health among underserved populations in low-and middle-income countries (LMICs) as well as the United States. 3,4 Although data to support this assertion are limited, medical students who completed a rotation in an LMIC have reported increased cost-consciousness, cultural competency, and public health awareness. 5 Additionally, the data indicate that such experiences can enhance both clinical skills (when the trainee is a clinician and has worked in a clinical setting) and intention to work with underserved populations in primary care specialties in the trainees' home countries or LMICs.…”
Section: Introductionmentioning
confidence: 99%
“…International collaborations and interactions between medical institutions occur frequently in the fields of research and clinical training, while less frequently in undergraduate medical education (Armstrong & Fischer 2001;De Vries et al 2002;Imperato 2004;Margolis et al 2004;Finkel & Fein 2006). To our knowledge, no international partnerships between medical schools have been described in the field of psychosocial education and professional skills.…”
Section: Practice Pointsmentioning
confidence: 98%
“…Many supporting organisations offer short-term volunteers some basic predeparture educational materials, such as about health concerns for volunteers and local culture 23 24. However, there is a wide range of issues requiring consideration, training and preparation, and short-term medical volunteers may not be aware of the breadth of these topics or of potential consequences if any are neglected.…”
Section: Introductionmentioning
confidence: 99%